2011
DOI: 10.1002/jwmg.252
|View full text |Cite
|
Sign up to set email alerts
|

Food resource availability for American black ducks wintering in southern New Jersey

Abstract: Midwinter waterfowl survey data indicates a long-term decline in the number of wintering American black ducks (Anas rubripes), potentially due to habitat limitations. In order for future estimates of carrying capacity to be determined, it is critical that regional food availability is estimated. We collected pairs of habitat core samples (n ¼ 510) from 5 habitat types in southern New Jersey, USA, during October, January, and April 2006-2008 to estimate resource availability and variability. We collected upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(72 citation statements)
references
References 21 publications
7
62
3
Order By: Relevance
“…Although black ducks are one of the more extensively studied waterfowl species, little is known about their nocturnal behavior. Studies of black duck movement using radio telemetry have reported nocturnal activity (Albright et al 1983;Hickey and Titman 1983;Morton et al 1989b;Cramer 2009) and in some cases different habitat use patterns between diurnal and nocturnal periods (Conroy et al 1986;Morton 2002). However, researchers have never quantified the actual behavior exhibited across all time periods.…”
mentioning
confidence: 99%
“…Although black ducks are one of the more extensively studied waterfowl species, little is known about their nocturnal behavior. Studies of black duck movement using radio telemetry have reported nocturnal activity (Albright et al 1983;Hickey and Titman 1983;Morton et al 1989b;Cramer 2009) and in some cases different habitat use patterns between diurnal and nocturnal periods (Conroy et al 1986;Morton 2002). However, researchers have never quantified the actual behavior exhibited across all time periods.…”
mentioning
confidence: 99%
“…We did not model uncertainty in the energy content of waterfowl foods, which could increase variation in energy supply by !10% and likely closer to 30-40% . We did not account for niche differentiation in habitat use, nor species-specific dietary preferences, but focused on habitat and food types selected by black ducks (Cramer et al 2012); this probably had a minimal influence on the outcome of the model given that black ducks comprise the majority of energetic demand at Forsythe. We also did not model depletion through degradation or consumption by nontarget species such as shorebirds or include foraging effectiveness or thresholds (Central Valley Joint Venture 2006, Miller et al 2014Hagy and Kaminski 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We used data from Cramer et al (2012), Goldstein et al (2016), Fino et al (2017), and newer unpublished data to evaluate foraging resources in high marsh, low marsh, mudflats, subtidal habitats, forested wetlands, and freshwater impoundments within our study area. We used an average value for salt marsh habitats to estimate energy availability in unclassified salt marsh.…”
Section: Quantifying Energy Supplymentioning
confidence: 99%
See 2 more Smart Citations